Electromagnetic Cell Current Modulation Via Emedica For Oral Health Improvement In HIV-Positive Patients: A Pilot Study On Lesion Resolution, Salivary Immunity, And Quality Of Life (International Journal of Environmental Sciences, 2025)
Background:Oral health complications remain common in HIV-positive individuals despite effective antiretroviral therapy (ART). These include candidiasis, aphthous ulcers, periodontal disease, and salivary gland dysfunction, which persist due to chronic immune activation and epithelial dysregulation.Objective:To evaluate the clinical efficacy of Electromagnetic Cell Current Modulation (ECCM) via eMedica in improving oral health parameters in HIV-positive patients undergoing stable ART.Methods:This quasi-experimental, pre-test/post-test pilot study involved 20 HIV-positive adults with oral lesions or xerostomia. Participants underwent 3 weekly ECCM sessions using eMedica for 8 weeks. Outcomes included clinical oral lesion scores, salivary flow rate, salivary IgA, oral pain scale, and OHIP-14 (Oral Health Impact Profile) for quality of life.Results:Significant reductions were observed in mean oral lesion scores (by 40%, p < 0.01), xerostomia symptoms (salivary flow rate increased by 32%, p < 0.05), and VAS pain scores (decrease by 35%). OHIP-14 scores improved across physical discomfort, functional limitation, and psychological domains.Conclusion:ECCM via eMedica showed promise in enhancing oral immunity and reducing symptom burden in HIV-positive individuals. These preliminary findings support the potential of bioelectromagnetic therapy in oral healthcare and warrant larger randomized controlled trials.